2019
DOI: 10.1016/j.jaad.2019.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Galactose-deficient IgA1 in skin and serum from patients with skin-limited and systemic IgA vasculitis

Abstract: Background: IgA-vasculitis (IgAV) encompasses a systemic form involving kidneys, gut, skin or joints, and a skin-limited form. One characteristic feature of systemic IgAV is deposition of galactosedeficient IgA1 (GD-IgA1) in kidneys (as in IgA-nephropathy). The relevance of GD-IgA1 for cutaneous vasculitis is unknown. Objective: We investigated if GD-IgA1 is deposited perivascularly in systemic and also skin-limited IgAV, and if its serum levels differ between both forms. Methods: In a case control study, depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…Reduced galactosylation in the O-glycan site of the hinge region of IgA1 was detected in patients with IgAV, especially IgAV-N (63,86,87). Recent findings of Gd-IgA1in the cutaneous lesions and clinically uninvolved skin in skin-limited IgAV further confirmed its role in IgAV (62). The serum level of Gd-IgA1-specific IgG is associated with disease activity and renal involvement (85).…”
Section: Galactose-deficient Iga1 and Its Autoantibodiesmentioning
confidence: 88%
See 3 more Smart Citations
“…Reduced galactosylation in the O-glycan site of the hinge region of IgA1 was detected in patients with IgAV, especially IgAV-N (63,86,87). Recent findings of Gd-IgA1in the cutaneous lesions and clinically uninvolved skin in skin-limited IgAV further confirmed its role in IgAV (62). The serum level of Gd-IgA1-specific IgG is associated with disease activity and renal involvement (85).…”
Section: Galactose-deficient Iga1 and Its Autoantibodiesmentioning
confidence: 88%
“…And some clinical studies suggested that the serum levels of Gd-IgA1 or Gd-IgA1-CIC in IgAV patients without nephritis are the same against healthy controls ( 63 , 86 ). However, in a recent study, Gd-IgA1 was detected using KM55 staining in the skin of IgAV patients without nephritis ( 62 ). The result suggested that Gd-IgA1 are important in both systemic and organ limited IgAV.…”
Section: Immunopathogenesis Of Igavmentioning
confidence: 97%
See 2 more Smart Citations
“…In IgAV, galactose-deficient IgA1 (Gd-IgA1) can be detected not only in the serum but also in the skin and kidney tissue ( Neufeld et al, 2019 ; Oni and Sampath, 2019 ; Zhang et al, 2020 ), and IgA1-containing immune complexes, especially IgA1 accumulation in vessel walls, promote the development of IgAV. A multi-hit hypothesis is generally considered to illustrate the role of Gd-IgA1 in the pathogenesis of IgAV.…”
Section: Immunoglobulin A-containing Immune Complexesmentioning
confidence: 99%